PENGARUH LABELISASI HALAL TERHADAP KEPUTUSAN PEMBELIAN HAND SANITAIZER SC JOHNSON PUMP PADA SAAT PANDEMI COVID 19 - Mulyani Rizki (Jurnal Ilmiah Manajemen, Bisnis dan Kewirausahaan, 2021)
In accordance with Indonesian Government regulations no. 69 of 1999 concerning advertising and labeling article 2 paragraph 1 which reads "that every company or individual who wants to produce or import products into Indonesian territory for trade is obliged to put a label on or inside the product packaging". Then in 2014 appeared Law no. 33 of 2014 regarding halal assurance of a product which requires producers to register their products for halal testing by the MUI (Indonesian Ulema Council) the inclusion of "Halal" has been decided and regulated with the Ministry of Religion and Ministry of Health No. 427/MENKES/SKB/VIII/1985 . This is one of the responsibilities of producers to Muslim consumers in Indonesia. There is still one other institution tasked with specifically overseeing the products that will be consumed by Muslims, the institution is (LPPOM-MUI) the Drug and Food Circulation Supervision Agency under the auspices of the Indonesian Ulema Council. One of the goals of the government to make the constitution is to guarantee and protect Muslims in Indonesia. Judging from the above phenomena, purchasing decisions that include Halal Labeling can be taken into consideration when purchasing an item or product. The purpose of this study was to find out how the effect of Halal Labeling on the purchase decision of the Johnson Pump Hand Sanitizer during the Covid 19 pandemic. The number of samples used in this study was 50 respondents, this study used a quantitative approach. The data collection technique in this study used a questionnaire, and the sampling technique used the purposive sampling method using the hair formula. The data obtained is then processed with SPSS 22.0 The results of this study show the t count > t table (11,463 > 1,67793) and a significance value of 0.000 < 0.05, it can be concluded that the hypothesis states that the results of the halal labeling variable (X1) have a positive and significant effect on purchasing decisions. hand sanitizer sc johnson pump during the covid 19 virus pandemic.